Q) Find X in terms of a b, and c: \frac{a}{\times - a} + \frac{b}{\times - b} = \frac{2 c}{\times - c}, X ≠ a, b, c

Ans:

Given equation is:

\frac{a}{(\times - a)} + \frac{b}{(\times - b)} = \frac{2 c }{(\times - c)}

\frac{a (\times - b) + b (\times - a)}{(\times - a) (\times - b)} = \frac{2 c }{(\times - c)}

∴ [a (X – b) + b (X – a)] (X – c) = 2 c (X – a) (X – b)

∴ (a X – a b + b X – a b )(X – c) = 2 c (X – a) (X – b)

∴ (a X + b X – 2 a b) (X – c) = 2 c (X2 – a X – b X + a b)

∴ a X2 + b X2 – 2 a b X – a c X – b c X + 2 a b c = 2 c X2 – 2 a c X – 2 b c X + 2 a b c

∴ a X2 + b X2 – 2 c X2 – 2 a b X + a c X + b c X = 0

∴ X (a X + b X – 2 c X – 2 a b  + a c  + b c)  = 0

∴ X [ X (a  + b  – 2 c ) – (2 a b  – a c  – b c )] = 0

∴ X = 0 and X (a + b  – 2 c ) – (2 a b  – a c  – b c ) = 0

∴ X = 0 and X = \frac{(2 a b  - a c  - b c )}{(a  + b  - 2 c)} 

Therefore, X = 0 and X = \frac{(2 a b  - a c  - b c )}{(a  + b  - 2 c)}  are the two roots of the given equation.

Please press the “Heart” button if you like the solution. 

Leave a Comment

Your email address will not be published. Required fields are marked *

Scroll to Top